XORIJIY DAVLATLARNING ADVOKAT STAJYORI FAOLIYATINI O`RAGINISH VA MILLIY QONUNCHILIKKA IMPLEMENTATSIYA QILISH - Xomidova Sarvinoz Yusup qizi (TADQIQOTLAR.UZ, 2023)
ABSTRACT: The legal status of a trainee lawyer, the rights and responsibilities of a trainee lawyer and his role in legal practice, the procedure for training a trainee lawyer, registration of an internship, issues of introducing experience in the work of a trainee lawyer of foreign countries into national legislation.